Violación del Principio de Interés Superior del Niño por el no reconocimiento de la adopción homoparental - Macas Silva, Jessenia Karina (2023)
The principle of the Best Interest of the Child aims to ensure the exercise of the rights of minors, implemented through Conventions and International Treaties subscribed by Ecuador, based on Article 44 of the 2008 Constitution. Additionally, the positive results observed in other countries where this type of adoption has opened up the possibility for children to be raised in a home that can meet their economic and emotional needs serve as a basis. With this background, the theme of the violation of the Best Interest of the Child through the denial of same-sex adoption is addressed, emerging as the general objective of this investigative work: to determine the effects of violating the Best Interest of the Child due to the lack of same-sex adoption. Regarding the level of depth, the study was based on a descriptive approach, as it proceeded to characterize the problem. The historical-logical method was applied, enabling the compilation of background information and the evolution of the addressed theme. The dogmatic-legal method could not be overlooked, and lastly, the comparative method was employed, allowing for the comparison of legislation from neighboring countries that have regulated this legal framework. Interviews were conducted to obtain results based on expert opinions, leading to the conclusion that the approval of same-sex adoption, if granted, would be in favor of the children and adolescents, creating new opportunities for abandoned minors to have a family that meets their psychological, economic, and protective needs.